The Influence of Accessibility And Facilities on Visitor Satisfaction in Mangrove Forests Pantai Indah Kapuk - Sulistio, Tri Djoko; Septiani, Thalia (Jurnal Penelitian Pariwisata, 2018)
Green nature in particular in Angke Kapuk Nature Park is a natural conservation area that is used for natural tourism activities and centered on the development of ecotourism. This mangrove forest nature park is a natural conservation area dominated by mangrove vegetation. Nature Park is very influenced by several things, especially accessibility and facilities provided. This research purposes to determine the effect of accessibility and existing facilities in Taman Wisata Alam to visitor satisfaction. The method of analysis used in this research is descriptive and quantitative method of regression. This method is do so that it can give conclusion and picture how accessibility and facility can influence visitor satisfaction. Based on the results of research on the Influence of Accessibility and Facilities to the Mangrove Forest Visitor Satisfaction in Pantai Indah Kapuk, it can be seen that the level of influence given variable X1 (Accessibility) to variable Y (Visitor Satisfaction) is 23.8% and the level of influence given variable X2 (Facility) to variable Y (Visitor Satisfaction) is equal to 76,3%. Therefore, managers should pay more attention to aspects that affect customer satisfaction